The Citric Acid Cycle: Historical Discovery, Biochemical Mechanisms, and Its Impact on Life Sciences - Lu, Lan (Journal of Contemporary Medical Practice, 2025)
With the rapid development of metabolomics and systems biology, scientists have made significant strides in exploring the regulatory mechanisms of the citric acid cycle, its associations with various diseases, and its applications in bioengineering. This paper reviews the historical discovery of the citric acid cycle, analyzes its biochemical mechanisms, and discusses its pivotal role in modern life sciences. By examining breakthroughs in early metabolic research, particularly advancements in glycolysis, citric acid metabolism, and enzymology, this paper reveals how the citric acid cycle was discovered based on the foundational work of previous studies. It also elaborates on how this scientific breakthrough has propelled theoretical innovations in the fields of metabolism and cell biology. Through a comprehensive analysis of this milestone discovery, the paper aims to highlight the fundamental position of the citric acid cycle in life sciences and its lasting impact.